Polymorphism in serotonin receptor 3B is associated with pain catastrophizing. - Emilia Horjales-Araujo (Public Library of Science (PLoS), 2013)
Pain catastrophizing, a coping style characterized by excessively negative thoughts and emotions in relation to pain, is one of the psychological factors that most markedly predicts variability in the perception of pain; however, only little is known about the underlying neurobiology. The aim of this study was to test for associations between psychological variables, such as pain catastrophizing, anxiety and depression, and selected polymorphisms in genes related to monoaminergic neurotransmission, in particular serotonin pathway genes. Three hundred seventy-nine healthy participants completed a set of psychological questionnaires: the Pain Catastrophizing Scale (PCS), the State-Trait Anxiety Inventory and Beck's Depression Inventory, and were genotyped for 15 single nucleotide polymorphisms (SNPs) in nine genes. The SNP rs1176744 located in the serotonin receptor 3B gene (5-HTR3B) was found to be associated with pain catastrophizing scores: both the global score and the subscales of magnification and helplessness. This is the first study to show an association between 5-HTR3B and PCS scores, thus suggesting a role of the serotonin pathway in pain catastrophizing. Since 5-HTR3B has previously been associated with descending pain modulation pathways, future studies will be of great interest to elucidate the molecular pathways involved in the relation between serotonin, its receptors and pain catastrophizing.